The Representations of Self-Love in Justin Bieber’s Love Yourself - Sarmi, Ni Nyoman; Rahmansyah, Muhammad Ilham; Ramadhani, Asjad Nina Hanan; Zahra, Shellamita; Pasopati, Rommel Utungga (Journal Corner of Education, Linguistics, and Literature, 2024)
The song of Love Yourself by Justin Bieber talks about the importance of self-love and acceptance by encouraging any audience to prioritize their own needs and well-being, rather than seeking validation from others. Through the lyrics, Bieber emphasizes the idea that love and respect start from within oneself. Self-love should be focused by letting go of toxic relationships and negative influences and to pay more attention to each person’s own growth and happiness. By answering the question of how may self-love be represented on Justin Bieber`s Love Yourself?, the song's message is particularly relevant in today's world where social media and external pressures often dictate how people perceive themselves. Love Yourself serves as a powerful reminder that self-love and acceptance are key to mental and emotional well-being. In conclusion, Love Yourself is a powerful song that promotes self-love and acceptance including pushing out any negativity and toxic influence.